What is known about mental health and US federal housing subsidy programs? A scoping review - Rick DeVoss; Jeremy Auerbach; Natalie Banacos; Adriana Burnett; Oluwatobi Oke; Stephanie Pease; Courtney Welton-Mitchell; Marisa Westbrook; Katherine L. Dickinson (Elsevier, 2022)
US federal housing subsidy programs have the potential to shape mental health outcomes for millions of low-income residents. Four characteristics of housing can influence mental health outcomes: cost, conditions, consistency, and context (the 4Cs). We use this framework to structure a scoping review focused on assessing what we know about how U.S. federal housing subsidy program affect mental health outcomes, and how those effects may operate through the 4C pathways. We identified 1203 peer-reviewed articles published between 2003 and 2020 that met our search criteria. A multi-phase screening process narrowed this down to 31 papers that met our eligibility criteria (examining U.S. subsidized housing and evaluating mental health outcomes). The full texts of these articles were reviewed and coded for study location, methods (including comparison groups, if present), housing programs studied, mental health outcomes, and factors related to each of the 4Cs. Most of the included articles (22/31) used quantitative methods, and a majority compared residents using different types of housing assistance (23/31) while only 7/31 included a comparison with individuals living in unsubsidized housing. Overall, results show that housing assistance has mental health benefits, and that these benefits vary across program types. The 4C framework helps to elucidate mechanisms underlying these effects. For example, residents who move from public housing to voucher-based housing (for example, through the well-studied Moving to Opportunity experiment) experience changes in neighborhood context that can be positive or negative (decrease in neighborhood violence but also decrease in social cohesion), along with less housing consistency and potentially higher utility costs. Future studies should focus on tradeoffs among the 4Cs, application of strong causal inference methods, comparisons between subsidized and unsubsidized housing, and longitudinal effects of redevelopment programs like the Choice Neighborhoods Initiative. This evidence can inform housing subsidy policy design to improve resident's mental health.